2013
DOI: 10.1007/s00705-013-1901-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Korean porcine sapeloviruses

Abstract: To evaluate the prevalence and genetic diversity of porcine sapeloviruses (PSVs) in Korea, a total of 100 diarrhea fecal samples from pigs were analyzed by RT-PCR and nested PCR assays with primer pairs specific for the VP1 gene. Overall, 34 % of the diarrhea samples tested positive for PSV, and a high proportion of infections occurred along with a variety of other enteric viruses and bacteria. Genomic and phylogenetic analysis of the VP1 genes revealed pronounced genetic diversities between PSVs from Korean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…SV-A strain KS04105 used in this study was isolated from faecal samples of diarrhoeic piglets from South Korea (Son et al , 2014a, b). This strain was passaged eight times in LLC-PK cells, including isolation, adaptation and triple plaque purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SV-A strain KS04105 used in this study was isolated from faecal samples of diarrhoeic piglets from South Korea (Son et al , 2014a, b). This strain was passaged eight times in LLC-PK cells, including isolation, adaptation and triple plaque purification.…”
Section: Methodsmentioning
confidence: 99%
“…This strain was passaged eight times in LLC-PK cells, including isolation, adaptation and triple plaque purification. Isolated viruses were confirmed as PSVs based on immunofluorescence assay (IFA), RT-PCR and transmission electron microscopy (Kim et al , 2016; Son et al , 2014a, b). …”
Section: Methodsmentioning
confidence: 99%
“…A recent Spanish study has demonstrated that SV-A is detected in the fecal samples from asymptomatic pigs and its infection has an age predilection to postweaning pigs [10, 14, 15]. In Korea, SV-A infections are common in pigs with diarrhea [12]. However, the occurrence and genetic diversity of SV-As in fecal samples from asymptomatic pigs and age predilection in both diarrhea and asymptomatic pigs are largely unknown.…”
mentioning
confidence: 99%
“…To determine the exact occurrence of SV-A infections across all age groups and their association with diarrhea, 110 fecal specimens from diarrheic or non-diarrheic pigs from previously SV-A positive farm [12] were collected during the winter of 2011 (Table 1…”
mentioning
confidence: 99%
See 1 more Smart Citation